Kebangkitan Penggunaan Candi Di Banyuwangi - Poniman Poniman (Jayapangus Press, 2021)
The existence of Hindus in the archipelago was mostly centered on Java at first. This can be seen historical evidence in the form of a temple that is still remaining. However, actually the temple is a continuation of the sacred buildings in the previous civilization. There was a change in the treatment of the temple at that time because the worshipers had changed their understanding as a result of the new theological understanding he was introducing. Humans in carrying out religious traditions coupled with their level of intelligence, they will always reduce what exists and will create new civilizations to free them from the confinement of previous traditions. Likewise, the reappearance of the use of temples as part of Hindu religious life in Banyuwangi, which he had long abandoned as a means of rituals as a sign of revival. So it raises problems that need to be researched related to